Analysis of the role of a writing-to-learn assignment in student understanding of organic acid–base concepts. Issue 2 (25th February 2019) - Schmidt-McCormack, Jennifer A.; Judge, Jessyca A.; Spahr, Kellie; Yang, Ellen; Pugh, Raymond; Karlin, Ashley; Sattar, Atia; Thompson, Barry C.; Gere, Anne Ruggles; Shultz, Ginger V.
Abstract : Acid–base chemistry is a foundational topic that is taught in courses across the chemistry curriculum. Students often have difficulty distinguishing between the different theories of acid–base chemistry—Brønsted–Lowry and Lewis acid–base chemistry—and applying these two definitions correctly in unfamiliar scenarios. To help students learn these definitions and be able to apply them, an acid–base Writing-to-Learn assignment was developed and evaluated. The Writing-to-Learn assignment involved a three-step process where students constructed an initial draft in response to a writing prompt, participated in peer review, and made revisions based on peer review feedback, before submitting a final draft. This process is informed by sociocultural theory applied to writing, which states that student learning of concepts increases through engagement with their peers' work and receiving peer feedback on their own writing. To test the efficacy of the acid–base writing assignment, an external assessment, comprised of conceptual questions related to acid–base chemistry and students' confidence when responding to them, was administered in two groups; a treatment group who completed the Writing-to-Learn assignment, and a comparison group who completed a separate assignment. Additionally, students who completed the Writing-to-Learn assignment were interviewed about their experiences. Regression analysis revealed that students in the treatment group had a greater increase in their conceptual understanding and confidence as compared to the students in the comparison group. The results demonstrate the students could successfully write about the Brønsted–Lowry and Lewis acid–base models separately, but were less successful with connecting these two concepts together in their writing. These results demonstrate the efficacy of Writing-to-Learn as an approach for promoting conceptual learning of acid–base chemistry.